Mangroves provide blue carbon ecological value at a low freshwater cost - Krauss, Ken W.; Lovelock, Catherine E.; Chen, Luzhen; Berger, Uta; Ball, Marilyn C.; Reef, Ruth; Peters, Ronny; Bowen, Hannah; Vovides, Alejandra G.; Ward, Eric J.; Wimmler, Marie-Christin; Carr, Joel; et al. (Scientific reports, 2022)
“Blue carbon” wetland vegetation has a limited freshwater requirement. One type, mangroves, utilizes less freshwater during transpiration than adjacent terrestrial ecoregions, equating to only 43% (average) to 57% (potential) of evapotranspiration ( ET ). Here, we demonstrate that comparative consumptive water use by mangrove vegetation is as much as 2905 kL H 2 O ha −1 year −1 less than adjacent ecoregions with E c -to- ET ratios of 47–70%. Lower porewater salinity would, however, increase mangrove E c -to- ET ratios by affecting leaf-, tree-, and stand-level eco-physiological controls on transpiration. Restricted water use is also additive to other ecosystem services provided by mangroves, such as high carbon sequestration, coastal protection and support of biodiversity within estuarine and marine environments. Low freshwater demand enables mangroves to sustain ecological values of connected estuarine ecosystems with future reductions in freshwater while not competing with the freshwater needs of humans. Conservative water use may also be a characteristic of other emergent blue carbon wetlands.